2019
DOI: 10.1155/2019/3265847
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Cardiovascular Risk Profile in Rheumatoid Arthritis Patients with Low Disease Activity

Abstract: Objective. Patients with rheumatoid arthritis (RA) have an excess risk of cardiovascular (CV) disease (CVD). The objective of the study was to compare CV risk profile in female and male RA patients with low disease activity. Materials and Methods. The study group consisted of 70 RA patients with continuous low disease activity and no CVD (54 women, 16 men) and 33 healthy controls of comparable age. The groups were assessed for blood pressure, serum amino-terminal pro-brain natriuretic peptide (NT-proBNP), caro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
0
13
2
1
Order By: Relevance
“… 25 Interestingly, in a group of RA patients with low disease activity and no history of cardiovascular disease, men had a significantly higher risk of cardiovascular-related mortality and atherosclerosis when compared to females. 26 The differences observed between our study and others could be related to diversity in genetic and socioeconomic factors, access to health care, comorbidities, and length of follow-up, among others.…”
Section: Discussioncontrasting
confidence: 76%
“… 25 Interestingly, in a group of RA patients with low disease activity and no history of cardiovascular disease, men had a significantly higher risk of cardiovascular-related mortality and atherosclerosis when compared to females. 26 The differences observed between our study and others could be related to diversity in genetic and socioeconomic factors, access to health care, comorbidities, and length of follow-up, among others.…”
Section: Discussioncontrasting
confidence: 76%
“…In one of the most recent works recently published, there was found significantly worst lesion of atherosclerosis in male RA patients compared with female RA patients. This study showed high and very high risk of fatal CVD in most male RA patients [17].…”
Section: Discussionmentioning
confidence: 50%
“…The prevalence of traditional cardiovascular risk factors is different between men and women 42 . Furthermore, disease activity may affect the burden of atherosclerosis 43 and it has been described that measures of disease activity seem to be worse in women than in men 44 . In addition, sex hormones may also be the basis for the differences, as it has been shown that estrogens decrease the inflammatory immune response 45 and hormone replacement therapy shows a beneficial effect on RA disease activity 46 .…”
Section: Discussionmentioning
confidence: 99%